Moisture use Efficiency of Dryland Crops as Influenced by Fertiliser Use II. Rabi Cereals - Singh, R P; Ramakrishna, Y S (Annals of Arid Zone, 2016)
Response of wheat (Kalyan Sona) and barley (EB3/Ratna) grown on conserved soil moisture to graded levels of nitrogen (20, 40, 60, 80 kg N/ha) and three methods of nitrogen application (broadcast, placement, 1/2 soil + 1/2 foliar) was studied at the Indian Agricultural Research Institute, New Delhi. for two consecutive seasons (1969-70 and 1970-71). Studies on moisture use efficiency revealed that both wheat and barley gave higher moisture use efficiency when fertilised with 40 kg N/ha. Half soil (drilled) + half foliar method of fertiliser application proved efficient with regard to moisture use efficiency In the case of wheat, whereas both placement and holf soil + half foliar methods showed their superiority over the broadcast method in the case of barley.